PEMANTAUAN KADAR LOGAM BERAT DALAM SEDIMEN DI PERAIRAN TELUK JAKARTA - Rochyatun, Endang; Rozak, Abdul (Makara Journal of Science, 2007)
Observation on Heavy Metals in Sediment of Jakarta Bay Waters. Observation on heavy metals in Jakarta Bay, from June and September 2003. Heavy metals Pb in sediment at the West have been conductet of Jakarta Bay Waters varied between Pb = 8,49-31,22 ppm, Cd =